Composite materials based on modified epoxy resin and carbon fiber - Gonçalez,Viviane (2006)
Epoxy resin networks have been modified with block copolymer of polybutadiene and bisphenol A diglycidyl ether (DGEBA)-based on epoxy resin. The epoxy resin modified with carboxyl-terminated polybutadiene presented improved impact resistance and outstanding mechanical performance in terms of flexural and tensile properties because of the presence of rubber particles homogeneously dispersed inside the epoxy matrix. This modified system also resulted in an improvement of mechanical properties of the corresponding carbon fiber based composites. The outstanding properties were attributed to a better interaction fiber-matrix, as indicated by SEM micrographs.